Epidemiology of cervical spine abnormalities in asymptomatic adult professional rugby union players using static and dynamic MRI protocols: 2002 to 2006. Issue 3 (2nd April 2008) - Castinel, B H; Adam, P; Milburn, P D; Castinel, A; Quarrie, K L; Peyrin, J-C; Yeo, J D
Abstract : Objective: In this study, the prevalence of abnormalities in the cervical spine of asymptomatic professional rugby players using both static and dynamic magnetic resonance imaging (MRI) in order to improve the detection of abnormalities and prevention of related injuries was investigated. Design: Prospective observational study. Setting: French professional rugby union clubs, between 2002 and 2006. Participants: 206 elite male adult players. Intervention: Static sagittal T2 and axial T2* fast spin echo (FSE), and dynamic sagittal single-shot FSE weighted MRI scans of the C2–C7 region were examined for the presence of abnormalities. Participants' spines were in supine neutral position for the static protocol but were allowed complete flexibility in a sagittal plane for the dynamic protocol. Main outcome measurements: The medulla-to-canal ratio (MCR) was measured at every vertebral disc level for both MRI methods. When observed, anatomical abnormalities were categorised. Results: Anatomical abnormalities mainly consisted of degenerative discopathy and were most frequently observed in players aged>21 years, as well as in players whose MCR was abnormally high based on medical expertise. Most MCRs that were initially assessed as intermediate with static MRI were subsequently assessed as abnormal with dynamic MRI assessment. Conclusions: Since dynamic MRI is more accurate than static techniques in examining the cervical spine, it contributes substantially to identifying the risk of spinal injuries in professional rugby players, and when used in association with clinical assessment, it can assist in preventing spinal injury.